Nilai-Nilai Pendidikan Akhlak Peserta Didik Terhadap Pendidik Dalam Kitab Ngudi Susilo Karya KH. Bisri Musthofa - Habibi, Wildan; Maharani, Fina (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
In today's modern life, humans really need moral education. And in the case of this research it is motivated by cases of social deviation, the existence of delinquency in which the perpetrators are students who are on average still under age, and also motivated by the condition of the fading culture of reading syi'ir in society, because syi'ir These contain many values ​​that are useful for the formation of moral education. What's more, with the current events in the world of education, it is often marked by an imbalance between worldly/material aspects and ukharawiyah/spiritual aspects. In this case, the researcher hopes to be able to give dedication in the world of education to overcome these basic problems. The book of Syi'ir ngudi susilo by KH. Bisri Musthofa written in Javanese pegon is a book that contains moral/educational teachings to form morals. In syi'ir ngudi Susilo also has the value of basic moral content that is useful for the formation of the growth and development of children's morals with akhlakul karimah. In terms of the value of moral education, students towards educators refer to the point of obedience, where the value of obedience is very important in the world of moral education, because it will have an important influence on the sustainability of the growth and development of students and the Indonesian nation. With the main moral value, namely obedience, students will grow up with noble character.